The mediating effect of mood on in-store behaviour among Muslim shoppers - Osman, Syuhaily; Ong, Fon Sim; Othman, Md Nor; Khong, Kok Wei (Emerald Group Publishing, 2014)
Purpose – The purpose of this paper is to examine the influence of atmospherics on in-store behaviour among Malay Muslim shoppers in Malaysia. The effect of age on shopping behaviour is tested using two age groups: 18-25 years and 50 years or older.